Climate Change Impacts on Irrigation Water Availability in Pante Lhong Irrigation Area, Peusangan Watershed Bireuen Regency - Maimun; Cut Azizah; Ridwan Iriadi (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2026)
Climate change poses a significant threat to water security, particularly for agricultural irrigation systems in monsoon-dependent regions. This study assesses the impact of climate change on irrigation water availability in the Pante Lhong Irrigation Area (DI Pante Lhong), Peusangan Watershed, Bireuen Regency, Aceh. Using a mixed-methods approach, the research analyzed decadal climate data (2014–2024) from the Meteorology, Climatology, and Geophysics Agency (BMKG), field measurements of river discharge, and interviews with farmers and irrigation officials. Results indicate a significant declining trend in annual rainfall (~-2.8% per year) and a consistent increase in maximum temperature (~+0.16°C per year). These changes have led to a substantial reduction in the reliable discharge (Q80) of the Peusangan River, particularly during the dry season (July-October), with decreases of up to 29%. A monthly water balance analysis projected a chronic water deficit for seven months (April-October), with the peak deficit in August (7.7 million m³), indicating that available water can meet only about 30% of irrigation demand during critical periods. The study concludes that climate change severely threatens the sustainability of rice farming in the region. Recommended adaptation strategies include infrastructure modernization, crop diversification, and strengthened water user institutions to enhance climate resilience.